The Effect Of Reading Strategy And Personality On Efl Students’ Reading Comprehension at STIE TRIBUANA - Tiara Noviarini (Universitas Lancang Kuning, 2021)
By interviewing four students at the Manajement Study Program in STIE Tribuana, the researcher found that the students face some problems when reading English texts. The problems found were important to be investigated because students’ reading comprehension play an essential part to improve their English ability from reading text. This research was conducted at STIE Tribuana. This research used descriptive quantitative approach. The respondents were divided into two groups: experimental group and comparison group. The experimental group was treated by using PQ4R strategy while comparison group was treated using CSR strategy. Each group consisted of 14 extroverted students and introverted students. The data were collected using reading test (35 items in the form of multiple choice) and personality questionnaire. The result revealed that there was no significant difference between students who use PQ4R and those who use Collaborative Strategic Reading (CSR) on their reading comprehension. The second one was there was no a significant difference between introverted students and extroverted students on their reading comprehension. The last one was that there was no a significant interaction between reading strategy and personality in their effect on students’ reading comprehension.